Short‐term safety and effectiveness of sugammadex for surgical patients with end‐stage renal disease: a two‐centre retrospective study. (12th November 2019) - Adams, D. R.; Tollinche, L. E.; Yeoh, C. B.; Artman, J.; Mehta, M.; Phillips, D.; Fischer, G. W.; Quinlan, J. J.; Sakai, T.
Summary: Sugammadex is a novel reversal agent for aminosteroid neuromuscular blocking drugs, especially rocuronium. Given its renal excretion, sugammadex is not recommended for patients with end‐stage renal disease; however, reports exist of its use in this group of patients. This two‐institutional retrospective observational study aimed to review the safety profile and effectiveness of sugammadex in surgical patients with end‐stage renal disease who required pre‐operative renal replacement therapy. Adult surgical patients with end‐stage renal disease requiring pre‐operative renal replacement therapy, who received sugammadex between April 2016 and January 2019, were studied. The primary outcome was the incidence of postoperative tracheal re‐intubation within 48 h. The secondary outcome was the incidence of deferred tracheal extubation in the operating theatre. One hundred and fifty‐eight patients were identified from 125, 653 surgical patients: 48 patients (30%) underwent renal transplantation and 110 (70%) underwent non‐renal transplantation procedures. There were 22 instances (14%) of deferred tracheal extubation due to surgical and/or pre‐existing medical conditions. Out of the 136 patients who had the tracheal tube removed at the end of the procedure, three patients had their trachea re‐intubated within 48 h: two patients developed pulmonary oedema resulting from volume overload; and one patient had worsening sepsis. No incidence of recurrence of neuromuscular blockade was observed. Of note, 24 (18%) patients were found to have incomplete neuromuscular blockade reversal with neostigmine but administration of sugammadex led to successful tracheal extubation. In conclusion, sugammadex appears to be safe and effective in adult patients with end‐stage renal disease receiving pre‐operative renal replacement therapy. 요약: Sugammadex는 아미노스테로이드(aminosteroid) 계열 신 경근 차단제(특히 rocuronium)의 새로운 역전제이다. 이 약제 의 신배설(renal excretion)을 감안할 때, sugammadex는 말 기 신장 질환 환자에게 권장되지 않는다. 그러나 해당 환자군 에 이를 사용한 보고들이 존재한다. 이 두 기관에서의 후향적 관찰 연구는 말기 신장 질환을 가졌으며 수술 전 신대체 요법 (renal replacement therapy)을 필요로 하는 수술 환자를 대 상으로 sugammadex의 안전성 프로파일과 효용성을 검토하 는 것을 목적으로 하였다. 수술 전 신대체 요법이 필요한 말기 신장 질환을 가진 성인 수술 환자 중 2016년 4월과 2019년 1월 사이에 sugammadex를 투여받은 환자를 대상으로 조사하였 다. 일차 평가지표(primary outcome)는 수술 후 48시간 이내 기관 재삽관(tracheal re‐intubation)의 발생률(incidence)이 었다. 이차 평가지표는 수술실에서의 기관 발관 유보(de‐ ferred tracheal extubation)의 발생률이었다. 125, 653명의 수술 환자 중 158명의 환자가 식별되었는데, 이 중 48명(30%)의 환자는 신장 이식을 시행받았고, 110명(70%)은 비신장 이식 (non‐renal transplantation) 수술을 받았다. 수술 및/또는 기 존 질병 상태(pre‐existing medical conditions)에 의한 기관 발관 유보가 22건(14%) 발생하였다. 수술 종료 시 기관 내 튜 브를 제거한 환자 136명 중, 3명의 환자가 48시간 이내에 기관 재삽관을 받았는데, 이 중 2명의 환자는 용적 과부하로 인한 폐 부종이 발생하였으며, 1명의 환자에서는 패혈증이 악화되었다. 신경근 차단의 재발은 관찰되지 않았다. 주목할 만한 것으로, 24명(18%)의 환자에서 neostigmine의 투여 후 불완전 신경근 차단 역전이 발생하였으나 sugammadex의 투여가 성공적인 기관 발관을 유도하였다는 점을 발견하였다. 결론적으로, sugammadex는 수술 전 신대체 요법을 받는 말기 신장 질환 을 가진 성인 환자에서 안전하고 효과적인 것으로 보인다.